2019
DOI: 10.1002/advs.201901018
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Fate of Intra‐Articular Injected Mesenchymal Stem Cells In Vivo in the Second Near‐Infrared Window for the Effective Treatment of Supraspinatus Tendon Tears

Abstract: Mesenchymal stem cells (MSCs) are capable of exerting strong therapeutic potential for the treatment of supraspinatus tendon tear. However, MSC therapy remains underutilized and perhaps underrated due to the limited evidence of dynamic visualization of cellular behavior in vivo. Here, second near‐infrared fluorescence imaging with biocompatible PbS quantum dots (QDs) provides a cellular migration map and information on the biodistribution and clearance processes of three densities of intra‐articularly injected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 78 publications
(112 reference statements)
2
25
0
Order By: Relevance
“…Although the authors did not evaluate the survival of these human MSCs within the joint space, they were able to demonstrate reduced pain and decreased cartilage damage among animals treated with human MSCs as compared with controls. Yang et al 58 characterized the biodistribution and distant major organ effects (ie, an assessment of toxicity and off-target effects) of murine MSCs delivered intra-articularly using a murine model of rotator cuff tear. Although the therapeutic cells in this study were not xenogeneic or transgenic cells and the intra-articular delivery of therapeutic cells in the setting of a supraspinatus repair is quite different than that in a knee joint (which has undergone a multilayered closure after arthrotomy), Yang et al did provide evidence that therapeutic MSCs can be cleared in vivo via the renal and gastrointestinal systems and that these cells exhibit no apparent inflammatory effects or toxicity on distant major organs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the authors did not evaluate the survival of these human MSCs within the joint space, they were able to demonstrate reduced pain and decreased cartilage damage among animals treated with human MSCs as compared with controls. Yang et al 58 characterized the biodistribution and distant major organ effects (ie, an assessment of toxicity and off-target effects) of murine MSCs delivered intra-articularly using a murine model of rotator cuff tear. Although the therapeutic cells in this study were not xenogeneic or transgenic cells and the intra-articular delivery of therapeutic cells in the setting of a supraspinatus repair is quite different than that in a knee joint (which has undergone a multilayered closure after arthrotomy), Yang et al did provide evidence that therapeutic MSCs can be cleared in vivo via the renal and gastrointestinal systems and that these cells exhibit no apparent inflammatory effects or toxicity on distant major organs.…”
Section: Discussionmentioning
confidence: 99%
“…Tracking the transplanted stem cells in vivo to provide evidence for therapy and promote the optimization of therapy Yang et al, 2019 AgInTe 2 QDs 700 nm/between 1,095 and 1,160 nm (excitation/emission)…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that there were no immune rejection reactions by the lymphoid organs when human MSCs were. It had been reported that after transplantation, most MSCs are filtered by liver, kidney and lung 40 . Keeping these things in mind, in the present study, we performed H&E staining of these organs and they did not show any abnormal findings.…”
Section: Discussionmentioning
confidence: 99%